1997
DOI: 10.1080/02841859709172108
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial primary intra-axial tumors in children

Abstract: In most cases, the exact diagnosis should be made by histological examination but it is important for treatment planning that the appropriate depiction of tumor extension and tissue characterization be made by MR and CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…A novel MRI phantom containing calcium and iron deposits supported our hypothesis that calcified regions produce a signal change in T1W images that allows them to be differentiated from deposits where iron is prevalent; both are known to appear hypointense on T2*W images. These results are in agreement with studies that had histological confirmation, two of which reported that calcium and other minerals appear hyperintense on T1W (24,30), three studies that reported that calcium and hemosiderin appear hypointense on T1W (31)(32)(33), and other three studies, which reported that noncalcified regions appear isointense on T1W (34)(35)(36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A novel MRI phantom containing calcium and iron deposits supported our hypothesis that calcified regions produce a signal change in T1W images that allows them to be differentiated from deposits where iron is prevalent; both are known to appear hypointense on T2*W images. These results are in agreement with studies that had histological confirmation, two of which reported that calcium and other minerals appear hyperintense on T1W (24,30), three studies that reported that calcium and hemosiderin appear hypointense on T1W (31)(32)(33), and other three studies, which reported that noncalcified regions appear isointense on T1W (34)(35)(36).…”
Section: Discussionsupporting
confidence: 91%
“…The resulting intracranial volume (ICV) masks were visually checked and corrected when necessary following the procedure described in (23) and further applied to the T1W sequence. The extracted brains from the T1W and T2*W sequences were bias-field corrected using N4 (24).…”
Section: Preprocessingmentioning
confidence: 99%
“…Among the supratentorial tumors, extraaxial tumors predominated with 51.98% which is attributed to the greater proportion of craniopharyngiomas (25%)[ 26 ] and extraaxial location of six cases of pilocytic astrocytomas (11.53%).…”
Section: Discussionmentioning
confidence: 99%